The leaf economics spectrum of triploid and tetraploid C4 grass Miscanthus x giganteus. (20th September 2022) - Li, Shuai; Moller, Christopher A.; Mitchell, Noah G.; Martin, Duncan G.; Sacks, Erik J.; Saikia, Sampurna; Labonte, Nicholas R.; Baldwin, Brian S.; Morrison, Jesse I.; Ferguson, John N.; Leakey, Andrew D. B.; Ainsworth, Elizabeth A.
Abstract: The leaf economics spectrum (LES) describes multivariate correlations in leaf structural, physiological and chemical traits, originally based on diverse C3 species grown under natural ecosystems. However, the specific contribution of C4 species to the global LES is studied less widely. C4 species have a CO2 concentrating mechanism which drives high rates of photosynthesis and improves resource use efficiency, thus potentially pushing them towards the edge of the LES. Here, we measured foliage morphology, structure, photosynthesis, and nutrient content for hundreds of genotypes of the C4 grass Miscanthus × giganteus grown in two common gardens over two seasons. We show substantial trait variations across M .× giganteus genotypes and robust genotypic trait relationships. Compared to the global LES, M .× giganteus genotypes had higher photosynthetic rates, lower stomatal conductance, and less nitrogen content, indicating greater water and photosynthetic nitrogen use efficiency in the C4 species. Additionally, tetraploid genotypes produced thicker leaves with greater leaf mass per area and lower leaf density than triploid genotypes. By expanding the LES relationships across C3 species to include C4 crops, these findings highlight that M .× giganteus occupies the boundary of the global LES and suggest the potential for ploidy to alter LES traits. SUMMARY STATEMENT: There is substantial variation in leaf‐level photosynthesis, N and P content, and leaf mass per unit area among Miscanthus × giganteus genotypes that contributes significantly to deviation in global leaf economics spectrum (LES) trait relationships. C4 species occupy a distinct niche of the LES.